Aplikasi Word Alignment Interlinier Bible dari Bahasa Ibrani/Yunani ke Bahasa Jawa dengan Menggunakan Algoritma Markov Chain Monte Carlo - Yunike Christina; Rolly Intan; Andreas Handojo (Jurnal Infra, 2019)
The Bible as the most popular and influential book, most printed and translated in various languages in the world. There are about 2,527 translations of parts of the biblical text, and 475 translations of the full text of the Bible. The purpose of all this is so that many people in the world can read the Bible in understandable languages. In this translation process, there is a possibility that there is a gap between the original language of the Bible and the language of translation. To answer this problem, an application is designed that applies the Markov Chain Monte Carlo algorithm and is packaged in efmaral tools to correlate the original language of the Bible with other languages known as the Interlinear Bible. The Intelinear Bible (ITL) is a means to see the meaning of words or phrases in the original text of the Bible. With the Interlinear Bible, the gap between the original language of the Bible and the translation language can be overcome. Interlinear bible is one application of word alignment which has a function to identify the relationship between words in parallel text in two different languages. Based on the results of this study, it can be seen that the addition of the first word randomly at the beginning of each verse can increase the recall results, precision and f-measure of the algorithm both the correlation between Javanese and Hebrew, as well as the correlation between Javanese and Greek. In addition, the more number of words correlated, can increasing recall, precision and f-measure value.